Rumen-protected methionine for dairy and beef cattle: current perspectives on methionine role, supplementation strategies, metabolism, health, and performance - Costa, Thais Correia; Nascimento, Karolina Batista; Danés, Marina de Arruda Camargo; Gionbelli, Mateus Pies; Duarte, Marcio de Souza (Frontiers in Animal Science, 2025)
Protein utilization by ruminants has unique characteristics due to the fractioning into ruminal degraded and undegraded portions. Because of these peculiarities, the amino acid (AA) profile that reaches the intestines for absorption differs from the known dietary protein sources. Among the essential AAs, methionine (Met) is the most limiting nutrient, especially in dairy cattle diets. Moreover, Met contributes to several biological processes, such as protein synthesis, epigenetic regulation, nuclear function, cellular redox potential, phospholipid homeostasis, among others. Hence, given these factors, there are considerable efforts to investigate the efficacy of this AA by employing technologies aimed at shielding it from rumen degradation in both dairy and beef cattle. In light of this, it is valuable to consolidate the findings available in the scientific literature regarding the performance, reproduction, fetal development, and health-related outcomes of rumen-protected methionine (RPM). This approach aims to offer a thorough and unbiased perspective concerning the potential outcomes achievable through the application of this technology. For instance, such insights can serve as a robust foundation for decision-making regarding the implementation of this technology in practical operations. Therefore, this literature review aims to: (1) explore Met metabolism and its importance as a precursor of methyl donors; (2) provide information on the existing methods for protecting Met in the rumen; and (3) compile research findings concerning the potential impacts of Met supplementation on milk production and composition, body weight gain, reproductive outcomes, immune function, and fetal development in both dairy and beef cattle.